Transformasi Fungsi Penutup Kepala Berbahan Kain sebagai Media Identifikasi Identitas Masyarakat dalam Aktivitas Seni Pertunjukan di Malang Raya - Robby Hidajat; Pujiyanto Pujiyanto; Tri Wahyuningtyas; Muhammad Afaf Hasyimy (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article explains the transformation of the function of cloth head coverings to identify people's identities in performing arts activities in Malang Raya. These cloth head coverings have types, shapes and techniques for wearing them, as well as meanings that determine the ethics of their use. This complexity is to be able to reveal the transformation of its use function in the artistic activity environment. Because the use of cloth head coverings has never been used to identify the social identity of people in greater Malang. This is the aim of this research, namely to reveal and explain the function of cloth head coverings used in artistic activities. The research method used is descriptive qualitative with data collection techniques in the form of interviews with key informants who are competent in the field of performing arts, observing the activities of wearing cloth head coverings used by the community in arts activities, and reviewing documents, in the form of pictures, photos or reliefs on temples. -temple. Data analysis uses the theory of continuity and change, symbolic interactional, and functional structure. The research results found two important factors that can indicate the social identity of the people of Malang Raya as follows: (1) Social status, (2) Symbolic, (3) and Spiritual.